2003
DOI: 10.1021/ja036152m
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Self-Organization of the Organic Semiconductor α-Quinquethiophene

Abstract: We show that thin films grown by vacuum sublimation, or formed by melted powders, of semiconductor alpha-quinquethiophene (T5) exhibit a hierarchical self-affinity organization that spans scales from tens of nanometers to hundreds of micrometers. T5 organization was investigated by X-ray diffraction (XRD), atomic force microscopy (AFM), and optical microscopy. XRD showed that vacuum-evaporated T5 films were characterized by a preferred orientation of the h00 planes parallel to the glass substrate. Melting of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
48
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 43 publications
5
48
1
Order By: Relevance
“…2). [41] This behavior is peculiarly different from that of the lower and higher homologues of the series, quaterthiophene (T4) and sexithiophene (T6), and undoubtedly has some relation to the different symmetry of oligomers with odd and even numbers of thiophene rings. Owing to its peculiar self-assembly properties, T5 forms very crystalline vacuum-evaporated thin films with high FET charge mobilities.…”
Section: Supramolecular Organizationmentioning
confidence: 96%
See 1 more Smart Citation
“…2). [41] This behavior is peculiarly different from that of the lower and higher homologues of the series, quaterthiophene (T4) and sexithiophene (T6), and undoubtedly has some relation to the different symmetry of oligomers with odd and even numbers of thiophene rings. Owing to its peculiar self-assembly properties, T5 forms very crystalline vacuum-evaporated thin films with high FET charge mobilities.…”
Section: Supramolecular Organizationmentioning
confidence: 96%
“…Owing to its peculiar self-assembly properties, T5 forms very crystalline vacuum-evaporated thin films with high FET charge mobilities. [41] However, minor structural modifications cause a drop in FET charge mobility by several orders of magnitude, even when the modified systems are able to self-organize in highly crystalline thin films. [42] Recently, we have also found that the electroluminescence properties of thiophene oligomers may be deeply affected by their self-assembly modalities.…”
Section: Supramolecular Organizationmentioning
confidence: 99%
“…The results presented show that the bulk-heterojunction approach, which is widely used in organic photovoltaic cells, can be successfully employed to select and tailor the functionality of field-effect devices, including ambipolar charge transport and light emission. porting material, [35] and P13 belongs to a class of perylene derivatives, which are well-studied electron-transporting materials. [36] The molecular structures of T5 and P13 and a schematic of the device architecture are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The two materials have been selected because of their transport and luminescence properties. ␣-5T is known as holetransporting material, 20 and from pure reference devices we extracted a hole mobility of 2.5ϫ 10 −2 cm 2 / V s. P13 belongs to a class of perylene derivatives, which are well-studied electron-transporting materials. The pure reference device had an electron mobility of 5 ϫ 10 −3 cm 2 / V s. The electron and hole mobilities of the pure materials lie within one order of magnitude, which is a prerequisite for achieving ambipolar current characteristics in a coevaporated film.…”
mentioning
confidence: 99%